Different people different styles: Impact of personality style in web sites credibility judgement - Ahmad, Rahayu; Wang, Jieyu; Hercegfi, Karoly; Komlodi, Anita (Springer Berlin Heidelberg, 2011)
Reliance on the Internet as a source of information has increased dramatically in recent years among information seekers.The reliability of information on the Internet can sometimes be questionable due to the absence of an editorial function.Users need to carefully consider the quality of the information before using it.The goal of this research was to study the process of credibility evaluation by users.We examined how personality styles influence the way people make credibility judgments when they are browsing online.Our results show that thinkers’ evaluation style were more fact based than intuitive users who relied more on their initial impression and prior experience with the websites.Perceivers gathered information from various sources before trusting information and forming perception on the credibility of authors and websites.Lastly the judgers tend to formed conclusions quickly.This resulted to filtering credible web sites based on the format and layout of the websites.